Spider Phobia: Neural Networks Informing Diagnosis and (Virtual/Augmented Reality-Based) Cognitive Behavioral Psychotherapy—A Narrative Review - Hinze, Jonas; Röder, Anne; Menzie, Nicole; Müller, Ulf; Domschke, Katharina; Riemenschneider, Matthias; Noll-Hussong, Michael (Frontiers in Psychiatry, 2021)
Recent fMRI studies on specific animal phobias, particularly spider phobia (arachnophobia), have identified a large variety of specific brain regions involved in normal and disturbed fear processing. Both functional and structural brain abnormalities have been identified among phobic patients. Current research suggests that both conscious and subconscious fear processing play a crucial role in phobic disorders. Cognitive behavioral therapy has been identified as an effective treatment for specific phobias and has been associated with neuroplastic effects which can be evaluated using current neuroimaging techniques. Recent research suggests that new approaches using virtual (VR) or augmented reality (AR) tend to be as effective as in vivo therapy methods and could expand treatment options for different medical or individual scenarios. Nevertheless, more research is necessary to deepen our understanding of the neural basis of arachnophobia and the most effective and lasting treatment procedures.